Estudo da produção e do envelhecimento do vinagre de laranja lima - Araújo, Lucynei Tenório de (2012)
Food industrialization may contribute positively when it allows the use of exceeding of crops, reducing wasting, contributing with incentive and diversification of agriculture production as well as adding value to production. Centered at the Mundau River Valey, the lime orange growth has in the Santana of Mundau County its major reference and main production in Northeastern Brazil. Despite the advantages and facilities, investments in the citrus agriculture in the State are still limited, resulting in lowproductivity and dispose of the exceeding products of the region. This work had the intention of developing technologies for full use of the exceeding production of lime orange of the State of Alagoas, evaluating the commercial viability and acceptation of the lime orange vinegar under different conditions of aging. The fermentative process was performed in two steps, the first one was the ethanolic fermentation and then the acetic fermentation, both being carried with chemical-physical and sensorial analysis. The lime orange’s ethanolic substrate obtained was according to the legislation and was well accepted by the consumers. Many studies were performed for the making of the vinegar, being the Orleans process – with a few modifications – the one with the best results. The first lime orange vinegar was obtained after a month and twenty six days, showing 4.41% acidity in acetic acid, 0.1 °GL residual alcohol by volume and pH 2.70. The other ones took less time to be made. The aging of vinegar was made with different treatments using pieces of wood of eucalyptus, pino, pine, cinnamon, pieces of cork, under physical conditions of presence and absence of light, with plastic bottles (PET type), aiming for a product with suave flavor and smell. The vinegar types were all in accordance with the demands of the Brazilian legislation for ethanol, acidity, ashes and pH analysis except the dry extract analysis of the vinegar under the one month long cork aging simulation. The vinegar under the light absent aging simulation showed color more intensively then the ones in the presence of light. The ones tested by the sensorial analysis of color and smell indicated lighter color and less acetic acid concentration, being more accepted. The sensorial analysis showed that the aging period should not exceed 42 days and that the pine generated a more accepted product. Such results allow value attachment to the lime orange culture at the region, fulfilling an environmental function avoiding loss and/or inappropriate discard of the product. The artisan way of obtaining vinegar is one of the technological alternatives for the use of the fruits, which can be utilized in rural areas or even, commercialized, attaching value to the culture with the diversification of a new product.